2020
DOI: 10.1556/032.2020.00016
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth and real exchange rate misalignments in the European Union

Abstract: We investigate the relationship between economic growth and real exchange rate (RER) misalignments within the European Union (EU) during the period of 1995–2016. In addition to the relative price level of GDP, we quantify an alternative indicator for the RER: the internal relative price of services to goods. We interpret RER misalignments as deviations from the levels consistent with the levels of economic development among the EU countries. Using pooled OLS and dynamic panel techniques, we find that within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…This is why this study chose to use the BEER model. From 1995 to 2016, Krekó and Oblath (2020) examined the connection underlying real exchange rate deviation and growth in the European Union. They discovered that, within the EU, overvaluation or undervaluation was correlated with lower or greater growth, which is mostly attributable to changes in countries with fixed exchange rate regimes, using pooled Ordinary Least Squares (OLS) and dynamic panel approaches.…”
Section: Review Of Theoretical Frameworkmentioning
confidence: 99%
“…This is why this study chose to use the BEER model. From 1995 to 2016, Krekó and Oblath (2020) examined the connection underlying real exchange rate deviation and growth in the European Union. They discovered that, within the EU, overvaluation or undervaluation was correlated with lower or greater growth, which is mostly attributable to changes in countries with fixed exchange rate regimes, using pooled Ordinary Least Squares (OLS) and dynamic panel approaches.…”
Section: Review Of Theoretical Frameworkmentioning
confidence: 99%
“…Most of the studies involving panel analysis of the real exchange rates misalignment's are concentrated on a single equation approach [21,27], such as panel ARDL (panel autoregressive distributed lag model) or DOLS (dynamic OLS panel model), while others neglect panel structure of the data by using euro area aggregated variables, see e.g. [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As far as we know from the previous studies, several authors have already found interactions between real exchange rates misalignment's and various macroeconomic variables, see e.g. [21,27,30], but there is no similar empirical study that considers the PVAR methodology within EU members and handles the instrument proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…18 Az EU-n belül lényegesen szorosabb a fejlettségi szint és az árszint közötti pozitív kapcsolat, mint ami világméretben tapasztalható; lásd erről Krekó & Oblath, 2018. Ebből pedig egyenesen következik az, amit az ábra fekete keresztmetszeti trendvonala mutat: ugyanebben az évben a nominális fejlettség a reálfejlettségnek csaknem pontosan négyzetes függvénye volt. A koefficiensek 1 százalékon szignifikánsak, és az ábrán is látható determinációs együtthatók rendkívül magasak.…”
Section: A Reálfejlettség Az áRszint éS a Nominális Fejlettség Alakulása Közötti Tapasztalati öSszefüggések Az Eu-banunclassified